Advancing Best Practices for Prescription Drug Labeling. (November 2015) - Bailey, Stacy Cooper; Navaratnam, Prakash; Black, Heather; Russell, Allison L.; Wolf, Michael S.
Objective: Problematic prescription drug labeling has been cited as a root cause of patient misunderstanding, medication errors, and nonadherence. Although numerous studies have recently been conducted to identify and test labeling best practices, the last systematic review on this topic was conducted a decade ago. The objective of this review was, therefore, to examine, summarize, and update best practices for conveying written prescription medication information and instructions to patients.Data Sources: English-language articles published from June 2005 to June 2015 were identified in MEDLINE and CINAHL by searching the following text words: ' medication OR prescription OR drug' AND 'label OR leaflet OR brochure OR pamphlet OR medication guide OR medication insert OR drug insert OR medication information OR drug information OR instructions ' AND ' patient OR consumer .' Reference mining and secondary searches were also performed.Study Selection and Data Extraction: A total of 31 articles providing evidence on how to improve written, prescription drug labeling for patient use were selected. Two reviewers independently screened articles, rated their quality, and abstracted data.Data Synthesis: Identified best practices included the use of plain language, improved formatting and organization, and more explicit instructions to improve patient comprehension. The use of icons had conflicting findings, and few studies tested whether practices improved knowledge or behaviors with patients' actual prescribed regimens.Conclusions: Future studies are needed to determine how specific modifications and improvements in drug labeling can enhance patient knowledge and behavior in actual use. Synthesizing best practices across all patient materials will create a more useful, coordinated system of prescription information.